19. RESULTS OF CIRCUMCISION SURGERY IN ADULTS WITH STAPLER AT VIETDUC UNVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the results of circumcision surgery in adults with Stapler at Viet Duc Friendship Hospital.Subjects and methods: All patients aged 18 years and older underwent penile stenosis surgery with Stapler at the Andrology Center - VietDuc University Hospital from January 2023 to March 2024.Results: Average age 28.65±11.42 years, the number of patients with comorbidities (hypertension and diabetes) accounted for 8.8%. Simple penile stenosis accounted for 44.1%, partial penile stenosis, short frenulum accounted for 13.2%, long foreskin accounted for 26.5% and fibrosis of the penile stenosis accounted for 16.2%. Complications during surgery included: mild edema (14.7%), bleeding due to incomplete closure of the surgical wound (5.9%). The average surgical time (excluding anesthesia time) was 8.35±2.24 minutes. The common Stapler size was size 26 (57.4%). Most patients had little postoperative pain, only 22.1% had severe postoperative pain and needed pain medication. Results after 1 week, the wound healed well, only 2.9% of cases had infection. Results after 3 months of surgery: 100% of patients had good wound healing: small scar width, not much protrusion, skin color similar to the surrounding area, no trace of staples, high aesthetics.Conclusion: Circumcision in adults with Stapler at VietDuc University Hospital gave good results after 1 week and after 3 months, is a safe, effective, aesthetic method, should be maintained and widely applied.
Keywords: Phimosis; Stapler